Problemas Intrafamiliares - Quispe Aimara, Bertha Fidelia (2017)
The objective of this research was to identify the intra-family problems in school students of Captain Giovanni Calles Educative Unit. The research was bibliographic, quantitative and of descriptive scope. Surveys were applied to 4 teachers and 74 students of fourth, fifth and sixth grade. Tables and statistical charts were used to present the results, with the interpretation. The bibliographic analysis allowed determining that the intra-family problems directly affect the learning. The results of the surveys allowed identifying that the intra-family problems that the children of the institution mentioned suffer are: loss of a family member, abandonment, separation of the parents, rejection and insecurity, domestic violence, addictions, demotivation, neglected basic needs, lack of affection, attention and economic problem….